Centrifuge model test study on micro-pile reinforcement of shallow foundation - Zixi Li; Ga Zhang (Soils and Foundations, 2023)
Micro-piles are an effective reinforcement measure for existing foundations in practice. A series of centrifuge model tests were conducted on different combinations of shallow foundation and micro-piles to investigate the reinforcement effect of micro-piles. The interaction mechanisms between the shallow foundation and micro-piles were analyzed on the basis of full-field image-based measurements of soil displacement. The micro-piles were proven to provide an effective reinforcement on the shallow foundation by decreasing the settlement, increasing the bearing capacity and making the soil deformation more uniform. The loading induces soil deformation within an area that expands gradually with a similar boundary shape and is widened by the micro-piles. The shallow foundation and micro-piles exhibit a significant nonlinear coupling effect on the bearing ability due to their interaction through the soil with the mechanism summarized with the strengthening effect and weakening effect. The micro-piles have a strengthening effect on the shallow foundation to increase the bearing resistance by constraining the horizontal deformation of the neighboring soil. The shallow foundation has a weakening effect on the micro-piles to decrease the bearing resistance by reducing the pile-soil relative displacement. The weakening effect and strengthening effect play the dominant role in turn as the total resistance increases.